1997
DOI: 10.1006/dbio.1997.8706
|View full text |Cite
|
Sign up to set email alerts
|

Graded and Lamina-Specific Distributions of Ligands of EphB Receptor Tyrosine Kinases in the Developing Retinotectal System

Abstract: Molecular gradients have been postulated to control the topographic mapping of retinal axons in their central targets. Based initially on their expression patterns, and more recently on functional studies, members of the EphA subfamily of receptor tyrosine kinases and their ephrin-A ligands have been implicated in the guidance of retinal axons along the anterior-posterior axis of the chick optic tectum. The report that a receptor of the EphB subfamily, EphB2/Cek5/Nuk/Sek3, is expressed in a high ventral to low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 50 publications
6
100
0
Order By: Relevance
“…This finding suggested that ligands that stimulate EphB2 phosphorylation must also be expressed in this tissue. Indeed, ephrin-B1 and ephrin-B2 are expressed in the embryonic retina (20,24). Consistent with binding of ephrin-B1 to EphB2 in the retina, we show here that not only EphB2 but also ephrin-B1 is phosphorylated on tyrosine in retinal tissue.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding suggested that ligands that stimulate EphB2 phosphorylation must also be expressed in this tissue. Indeed, ephrin-B1 and ephrin-B2 are expressed in the embryonic retina (20,24). Consistent with binding of ephrin-B1 to EphB2 in the retina, we show here that not only EphB2 but also ephrin-B1 is phosphorylated on tyrosine in retinal tissue.…”
Section: Discussionsupporting
confidence: 88%
“…onic retina is intriguing because these proteins have complementary patterns of expression; ephrin-B1 is most highly expressed in the dorsal retina, and EphB2 is most highly expressed in the ventral retina (Fig. 5, A and B) (20,24,25). However, we found that ephrin-B1 is also expressed at low levels in the ventral retina and that EphB2 is also expressed in the dorsal retina (Fig.…”
Section: Ephrin-b1 and Ephb2 In Vivo Tyrosine Phosphorylation Sitesmentioning
confidence: 66%
See 1 more Smart Citation
“…Exactly the same number of genes was found to be enriched in the dorsal retina, using the same criteria (SI Table 10). Five of the 10 most highly enriched ''dorsal'' genes were genes previously shown to be enriched in the dorsal retina: Tbx5, Ephrin B2 (Efnb2), COUP-TFII (Nr2f2), Raldh1 (Aldh1a1), and Cyb1b1 (13)(14)(15)(16)(17)(18). In addition, the two dorsal Ͼ ventral cone genes discussed above, Opn1mw (M-opsin), Smug1, and one additional cone gene, Arr3, were also found to be among the top 21 most dorsally enriched genes.…”
Section: Dorsal-ventral (D-v) Patterning Of Photoreceptor Genes Suggementioning
confidence: 99%
“…After CALI of ephrin-A5, tecta were dissected and incubated with 0.3 nM EphA3-AP for 30 min (24). After rinsing, tecta were fixed with 4% paraformaldehyde, and endogenous AP activity was heat inactivated at 65°C for 45 min.…”
Section: Animalsmentioning
confidence: 99%